2008
DOI: 10.1002/pssb.200844126
|View full text |Cite
|
Sign up to set email alerts
|

Study on the addition of nonmetal interstitial atoms to the yttrium lattice: formation of YBx, YCx and YNx alloys

Abstract: Yttrium is a rather rare and reactive met al. Due to these characteristics it absorbs important quantities of light atoms in its void spaces. Here, we present a study where B, C and N atoms are gradually incorporated into the octahedral interstices of Y. The idea is to model, by first‐principles calculations in a supercell approach, several stages of nonmetal assimilation in the yttrium lattice. In this case to develop YBx, YCx and YNx alloys. This study is limited to the cubic close‐packed stacking of Y and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…They reported an increase in Young's modulus of 87 GPa, 125 GPa and 160 GPa; for YB, YC, and YN, respectively. As a consequence, the Y-Y bond lengths with C remains constants a e-mail: mromero@ciencias.unam.mx essentially; while, a slight increase or contracting in these bond lengths is observed when B or N is incorporated [6]. For YB x with x = 4.0, Zhou et al reported 427 GPa [5].…”
Section: Introductionmentioning
confidence: 99%
“…They reported an increase in Young's modulus of 87 GPa, 125 GPa and 160 GPa; for YB, YC, and YN, respectively. As a consequence, the Y-Y bond lengths with C remains constants a e-mail: mromero@ciencias.unam.mx essentially; while, a slight increase or contracting in these bond lengths is observed when B or N is incorporated [6]. For YB x with x = 4.0, Zhou et al reported 427 GPa [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this type of Mg-O alloy, the elastic modulus increases to a value approximately 10% greater than that of pure Mg ( Table S2 ). It is hypothesized that the incorporation of nonmetal atoms in the interstitial spaces of magnesium may increase the Mg-O ionic bonding character and average Mg-Mg interatomic distance, which enhances the stiffness of magnesium 28 . The yield stress of the Mg-O alloy (~73 MPa) is also three times higher than that of pure Mg ( Fig.…”
mentioning
confidence: 99%